2018
DOI: 10.1080/03639045.2018.1513024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical excipients properties and screw feeder performance in continuous processing lines: a Quality by Design (QbD) approach

Abstract: Screw feeder performance is a critical aspect in continuous manufacturing processes. Pharmaceutical excipients, such as mannitol, microcrystalline cellulose, lactose monohydrate, and anhydrous dibasic calcium phosphate can present problems in ensuring a continuous stable feed rate due to their sub-optimal flow properties. In alignment with Quality by Design (QbD) goals, the aim of this work was to identify and explain critical sources of variability of some powder excipients delivery by screw feeding, in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Ratholes in the feed chute were observed for both K15M CR and K100M CR which prevented the refill from being completed. A similar phenomenon was observed in other feeder studies with different materials and equipment (Cartwright et al, 2013;Santos et al, 2018).…”
Section: Liw Feeder Studiessupporting
confidence: 88%
“…Ratholes in the feed chute were observed for both K15M CR and K100M CR which prevented the refill from being completed. A similar phenomenon was observed in other feeder studies with different materials and equipment (Cartwright et al, 2013;Santos et al, 2018).…”
Section: Liw Feeder Studiessupporting
confidence: 88%
“…Many studies have been conducted under process-relevant gravimetric feeding mode. To gain understanding of the material-feeder interaction, volumetric feeding studies have also been performed [19,21,31,41]. The volumetric feeding performance of the two polyols grades investigated in this study was found to be consistent across all the feeding strategies and process conditions tested and resulted in relatively high levels of mass flow.…”
Section: Effect Of Materials Attributes On Feeding Performancementioning
confidence: 74%
“…The bulk (BD) and tapped (TD) density of the powders were determined using the cylinder method [41] on a Pharma Test PT-TD200 (Pharma Test, Germany), and the derived Hausner ratio (HR) and Carr index (CI) were selected as flowability descriptors.…”
Section: Particle and Bulk Characterizationmentioning
confidence: 99%
“…Unmilled, milled, and micronized powders were included, as were a range of particle morphologies, including needles. The aim was to have materials both above and below the FFC of 3, which has been shown elsewhere to be a key parameter in determining acceptable performance in LIW feeders 35 . In addition, excipient materials were also chosen and were all expected to have higher FFC's than 3, as demonstrated in previous studies.…”
Section: Selecting Materials and Techniques For The Studymentioning
confidence: 99%